Magic Fingers: Easy Explanation of Units of Measurement to School Students - Barnogul Bobobekova (International Journal on Integrated Education, 2022)
The article introduces a new easy-to-use method of explain units of measures and their conversion. The method utilizes human fingers to convert units of measurements as a quick demonstration for increasing or decreasing units for distance, area and volume.